Pengembangan Sistem Informasi Geografis Berbasis Android Pada Wisata Daerah Lombok, Nusa Tenggara Barat - Ahmad Subki; Bahtiar Imran; Surni Erniwati (Fakultas Teknik Universitas Hamzanwadi, 2021)
Lombok Island is one of the tourist destinations in Indonesia that has the potential to be developed. Based on data from the NTB Provincial Tourism Office at the end of 2019, the number of tourist visits was 3,706,352 tourists, with details of 1,550,751 foreign tourists and 2,155,561 domestic tourists. Based on the 2018-2023 Strategic Plan, the Culture and Tourism Office of West Nusa Tenggara Province, the island of Lombok has potential tourism objects such as beach tourism, waterfalls, mountains, culinary, culture, religion, and others. However, not all existing tourist attractions are known by visiting tourists, both the location of tourist attractions or the distance traveled to tourist sites, so it is necessary to make efforts to increase the number of visitors who come to the island of Lombok through various efforts. One of the efforts that can be done is the application of an Android-based tourism system so that it can be accessed by foreign tourists or domestic tourists who can provide complete information about tourist information on the island of Lombok. The system development method used in this research is the Research and Development (RD) method. Geographic Information Systems with the Research and Development (RD) method can provide good results and can be proven from the limited test results getting an average result of 71.45% with